PTH-306 R1 rectal cancer: an analysis of survival. (22nd June 2015) - Joshi, HM; Ormsby, N; Chadwick, M; Scott, M; Samad, A; Rajaganeshan, R
Abstract : Introduction: Evidence has shown that a positive resection margin (R1) is a key determinant of subsequent local recurrence and a poor prognostic factor in rectal cancer. The aim of this study was to evaluate the outcomes of patients with R1 resection of rectal cancer. Method: Retrospective study of all patients operatively managed within our institution between April 2008–April 2013 for rectal cancer. Baseline demographics and multiple outcome measures recorded. Overall survival (OS), disease free survival (DFS) and recurrence were the primary outcome measures. Results: Overall there were 306 primary rectal cancers. 76% were grade T3/4 tumours. OS of 30 months. R1 rate was 16% (48 patients). 31 patients underwent APR, and 17 AR. 32 patients underwent neo-adjuvant treatment. In responders, overall survival was 55 months, with no EMV. In non-responders OS was 29 months, with EMV in 48%. In patients who did not receive NAC, OS was 23 months, with EMV in 74%. EMV is the strongest predictor for poor survival following R1 (p = 0.001). We found a correlation between number of positive nodes, and OS/DFS(p = 0.004). Conclusion: R1 rectal cancer is not an automatic death sentence. We have demonstrated relatively positive OS in this cohort. In particular, those who respond to NAC have the potential for very good OS and DFS, with the potential for remission. We have shown EMV to be the strongest predictor for poor survival. Perhaps these patients could benefit from intraoperative frozen section histo-pathological analysis and intraoperative radiotherapy to improve survival and reduce recurrence rate. Disclosure of interest: None Declared.